Indonesia - Public Expenditure and Financial Accountability : Public Financial Management Performance Report and Performance Indicators - World Bank (Washington, DC, 2012)
The Public Expenditure and Financial Accountability (PEFA) assessment for Indonesia was undertaken by a team of World Bank staff and consultants with close involvement of counterparts from the Government of Indonesia. The PEFA measurement framework has been developed after wide consultations with a group of donors, client countries, and international professional organizations. It provides an integrated, standardized, and indicator-led methodology to measure and monitor Public Financial Management (PFM) performance over time. Its objective is to help assess the performance of PFM systems, processes, and institutions in each country and provides broad measures of PFM performance relative to system characteristics. The scoring methodology, covering a set of thirty one high level indicators, emphasizes empirical and observable scores for each PFM area based on internationally recognized good practice. The framework was not designed to rank countries by means of an overall aggregate score for each country. The PFM performance report which supports the scores and brings together an analytical summary is not meant to judge policy actions of government nor provide explicit recommendations, but instead to support a strengthened approach to PFM reforms by facilitating dialogue between government and other stakeholders on PFM reforms.